Extended metaphor in the manipulative discourse - "Pankratova Svetlana A. " (Актуальные проблемы филологии и педагогической лингвистики, 2018)
Today the problem of public consciousness manipulation stays invariably topical and up-to-date. Within the bounds of the Theory of Positioning of such authors as E. Rice and G. Trout there is a discussion about the cognitive consciousness shift, when the mass consumerism era persuades people to base their opinions not on year-by-year experiential foundation, but without wasting energy on the in-depth analysis of the situation. The appearance of the Internet among the means of modern communication leads to a new type of mental framing and concept modelling. Now the word activated in consciousness call for an immediate cross-referencing reaction which directs the mental inquiry to a certain mental “file”. The Theory of metaphor proves to be very topical in this sense. Complex, extended metaphor becomes the mirror, reflecting the process of creation and adjusting of the imagery for the manipulative influence on the addressee. The article uses the method of frame modeling to demonstrate how the discourse manipulation is implemented. To perform this, as the author of the article presupposes, the new picture of the world including a new niche, position or mental one-unit or multi-unit frame is created in the addressee’s mind. Thanks to this the majority of semantic spheres of the English language are included in the “frame” structures modeling the conceptual sphere of addressees. It is significant that metaphoric modeling in manipulative discourse has not a random, arbitrary, but task-oriented character aimed at modifying the system of addressee’s beliefs. The exposure and study of the image potential of the English language is of practical value for the mental hygiene, viewed as the purity of mental concepts of the addressee. The summary states that extended metaphor is not very frequent in the English discourse, but it exemplifies purposeful task of modifying of the addressee’s picture of the world by means of substituting slot of one semantic sphere with other slots, convenient to the sender of the metaphoric message